Software Engineering: A Practitioner's Approach - Roger Pressman; Bruce Maxim (USA McGraw-Hill Education, 2020)
For almost four decades, Software Engineering: A Practitioner's Approach (SEPA) has been the world's leading textbook in software engineering. The ninth edition represents a major restructuring and update of previous editions, solidifying the book's position as the most comprehensive guide to this important subject.
Keywords: Software; Nonfiction; (ICE-2002) Industrial Projects